Grant Park the democratization of presidential elections, 1968-2008 - Nelson, Candice J. 1949- (Brookings Institution Press, 2011)
"Takes a look at American presidential elections from 1968 to 2008--a period of great change in American society in general--and explains how changes in technology, finance laws, party rules, political institutions, and the electorate itself have affected the selection process and might again in the upcoming election"--Provided by publisher.